Adolescents' perceptions and user experiences with a virtual reality-based alcohol prevention tool in Germany: A focus group study - Hrynyschyn, Robert; Prediger, Christina; Lyk, Patricia; Majgaard, Gunver; Helmer, Stefanie Maria; Stock, Christiane (Frontiers in Public Health, 2023)
Background Excessive alcohol consumption is a major public health problem, with substance use early in life contributing to higher levels of use later in life. Virtual reality (VR) is an innovative technology for alcohol prevention among adolescents that could solve the problem of insufficient outreach to the target group of young people. The co-created German Virtual LimitLab simulation is one of the few examples of VR-based alcohol prevention tools and consists of a virtual house party simulation. The aims of Virtual LimitLab are to increase the users' awareness of how social pressure can influence their own decision-making as well as to enable various actions and communication strategies in order to train competencies when dealing with alcohol. The present study thus aims to explore adolescents' content- and technique-specific perceptions of Virtual LimitLab in order to gain insights into user experiences and to test the prototype with the German target group. Methods Four semi-structured focus groups with adolescents aged 15–18 years (n = 13) were conducted and analyzed using thematic analyses. A user experience questionnaire (UEQ–S) was applied in order to quantitatively assess adolescents' satisfaction with Virtual LimitLab. Results Three main themes were identified (VR experience, content, and technical aspects). Participants positively assessed both the content and the technical aspects of Virtual LimitLab. This trend was also seen by the UEQ–S data, which yielded positive ratings for both pragmatic and hedonic quality. The broad variety of options in the simulation that allow the user to try new behaviors was perceived particularly positively. In general, Virtual LimitLab was regarded as an innovative tool that encourages adolescents to think critically about their personal alcohol consumption. Technical errors in the simulation and users' difficulties in identifying with the simulation were the main points of criticism. Conclusions Feedback from adolescent users revealed positive and therefore promising results when using Virtual LimitLab as a gaming alcohol-prevention tool. Some technical aspects still need to be improved in order to further refine the prototype, and suggestions for expanding the content of the application have already been made.